(untitled) - 1929-; Juster, Norton; Raschka, Christopher ([New York], 2005)
The kitchen window at her grandparents' house is a magic gateway for one imaginative little girl.
"Michael di Capua books."
Keywords: Windows; Fiction; Grandparent and child; Fiction